Culturally Responsive Traditional Games: A Constructivist Approach to Enhancing Elementary Science Motivation - Ni Luh Anggun Raya Damayanti; Muhammad Aqil; Surahman Wilade; Rizal Rizal; Ryan Andhika Pratama (Papanda Publisher, 2026)
This study investigated the effectiveness of traditional educational games in enhancing learning motivation among fourth-grade students in Natural and Social Sciences (IPAS) instruction. Employing a pre-experimental one-group pretest-posttest design, the research involved 13 students at SD Inpres 2 Balinggi, Central Sulawesi, Indonesia, during the 2025/2026 academic year. Learning motivation was measured using a validated 15-item questionnaire administered before and after implementing traditional game-based instruction on the